2019
DOI: 10.1097/ta.0000000000002567
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative computed tomography is poor in detecting tumors of the appendix among patients with acute appendicitis: A cohort study of 5,224 appendectomies

Abstract: BACKGROUND Neoplastic processes are among the known etiologies for acute appendicitis. While conservative treatment with antibiotics alone has been proposed as a treatment for uncomplicated appendicitis, the presence of tumors should be excluded when offering patients this option. The aim of this study was to assess the accuracy of computed tomography (CT) in detecting appendiceal tumors. METHOD Consecutive patients operated on for acute appendicitis be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Hospital stay tends to be longer in the antibiotic therapy group, and approximately 30% of patients treated with antibiotics were in need of appendectomy within 1 year [3,18,19]. Another important aspect to consider are appendiceal malignancies that are coincidentally found in 0.7-2.5% of histopathological evaluation of appendectomy specimens [22][23][24]. Treating patients with antibiotics can delay the diagnosis and lead to incurable cancer stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital stay tends to be longer in the antibiotic therapy group, and approximately 30% of patients treated with antibiotics were in need of appendectomy within 1 year [3,18,19]. Another important aspect to consider are appendiceal malignancies that are coincidentally found in 0.7-2.5% of histopathological evaluation of appendectomy specimens [22][23][24]. Treating patients with antibiotics can delay the diagnosis and lead to incurable cancer stages.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect to consider is appendiceal malignancies that account for up to 2.5% of the appendectomy specimens. There is a concern that antibiotic-only treatment may cause a delay in the diagnosis and management of incidental malignancies [35,36]. Uncomplicated AA should be treated conservatively during the COVID-19 pandemic, when possible, as per the recommendation of a recent meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although preoperative CT scans can be used in confirming the presence of appendicitis with high sensitivity [6], they are not great at identifying if the cause is neoplastic [10]. A cohort study was published in 2020 which concluded that even if CT scans cannot identify neoplastic causes, they cannot exclude them either [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although preoperative CT scans can be used in confirming the presence of appendicitis with high sensitivity [6], they are not great at identifying if the cause is neoplastic [10]. A cohort study was published in 2020 which concluded that even if CT scans cannot identify neoplastic causes, they cannot exclude them either [10]. On the other hand, if the tumor has lymph node involvement, distant metastasis, or features that suggest an underlying malignancy, a preoperative CT scan could give us some hints on the underlying etiology [11].…”
Section: Discussionmentioning
confidence: 99%